Testis-specific serine/threonine kinase dTSSK2 regulates sperm motility and male fertility in Drosophila - Ju Peng; Angyang Sun; Jie Zheng; Na Zhang; Xuedi Zhang; Guanjun Gao (Communications Biology)
Abstract Serine/threonine kinases of the TSSK (Testis-Specific Serine/Threonine Kinase) family play crucial roles in spermatogenesis and male fertility across species, but the underlying regulatory mechanism remains incompletely understood. In this study, we identified and characterized a novel TSSK homolog in Drosophila, named dTSSK2 (CG9222), which functions as the ortholog of human TSSK4. dTSSK2 is specifically expressed in the testis and localizes to individualization complexes during spermiogenesis. Disruption of dTSSK2 severely compromises sperm motility, leading to failed sperm transit into the seminal vesicle and male infertility. Phosphoproteomic analyses reveal that dTSSK2 coordinates sperm flagella assembly and motility by phosphorylating proteins involved in microtubule organization, organelle assembly, and flagella structure. Notably, dTSSK2 phosphorylates the substrate Gudu at Ser9, which partially contributes to individualization complex integrity and sperm motility. These findings elucidate the critical role of dTSSK2-mediated phosphorylation in regulating Drosophila male fertility.